Social Enterprises in Poland in the Face of Recent Crises - Tomasz Gardziński (Social Entrepreneurship Review)
Background: The research problem addressed in this study concerns the activities of social enterprises (SEs) within the framework of the social market economy (SME) in Poland during the crises triggered by the COVID-19 pandemic and the war in Ukraine.